2012
DOI: 10.1007/s13592-012-0185-2
|View full text |Cite
|
Sign up to set email alerts
|

Cocoon orientation in the nests of red mason bees (Osmia bicornis) is affected by cocoon size and available space

Abstract: International audienceProper orientation of cocoons in linearly structured nests can be crucial for the survival of hatching bees. Nevertheless, misoriented cocoons appear in nature in notable proportions. A detailed analysis of sex, space available for cocoon spinning, cocoon size, and nest diameter in the red mason bee (Osmia bicornis) showed that smaller males are more prone to misorientation than larger females. Generally, smaller individuals of both sexes are more often misoriented because smaller larvae … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 8 publications
0
9
0
Order By: Relevance
“…Solitary bees, thanks to their role in crop pollination and the possibility of managing them successfully (Bosch and Kemp 2002 ; Krunić and Stanisavljević 2006 ), are often used in ecological studies describing the effects of environmental stressors. The red mason bee ( Osmia bicornis Panzer), a widespread European species, is particularly widely studied concerning its general biology, nesting and development (Raw 1972 ; Radmacher and Strohm 2010 ; Seidelmann et al 2009 ; Szentgyörgyi and Woyciechowski 2013 ; Wasielewski et al 2011 ; Kierat et al 2017a ). Red mason bees, although considered rather as a species that nests above ground, can come into direct contact with both airborne contamination during foraging and pollution accumulated in the soil due to using soil for building the walls separating their cells containing offspring (Bosch et al 1993 ).…”
Section: Introductionmentioning
confidence: 99%
“…Solitary bees, thanks to their role in crop pollination and the possibility of managing them successfully (Bosch and Kemp 2002 ; Krunić and Stanisavljević 2006 ), are often used in ecological studies describing the effects of environmental stressors. The red mason bee ( Osmia bicornis Panzer), a widespread European species, is particularly widely studied concerning its general biology, nesting and development (Raw 1972 ; Radmacher and Strohm 2010 ; Seidelmann et al 2009 ; Szentgyörgyi and Woyciechowski 2013 ; Wasielewski et al 2011 ; Kierat et al 2017a ). Red mason bees, although considered rather as a species that nests above ground, can come into direct contact with both airborne contamination during foraging and pollution accumulated in the soil due to using soil for building the walls separating their cells containing offspring (Bosch et al 1993 ).…”
Section: Introductionmentioning
confidence: 99%
“…Seidelmann, Bienasch, and Pröhl (2016) reported that the mass of the cocoon is not affected by the length, diameter of the reed, and the number of cells in the nest is affected by both the diameter and length of the stem. Szentgyörgyi and Woyciechowski (2013) stated that the diameter affects the size of the cocoon in mm. In addition, the diameter of the stalk affects the ratio of emerged females to males, and in the lower diameters there is a higher number of males (Seidelmann, Ulbrich, & Mielenz, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…The nests architecture is typical for megachilid bees, which most commonly build linear nesting cells in dry, hollow stems or in wall cracks (Cane et al, 2007). A mixture of mud and secretions from the bees salivary glands are used for the division of the nest into cylindrical cells arranged linearly (Raw, 1972;Szentgyörgyi & Woyciechowski, 2013). The cells are supplied with pollen by the female on which it lays a fertilized (female-diploid progeny) or nonfertilized (male-haploid progeny) egg.…”
Section: Introductionmentioning
confidence: 99%